Math, asked by komalkekraha, 3 months ago

factorise by spilliting the middle term 9(x-2y)-4(x-2y)-13​

Answers

Answered by Abhisheshlove
0

Answer:

A little correction the right question is 9(x-2y)²-4(x-2y)-13​

Step-by-step explanation

Heya buddy,

Q. Factorise:

9(x-2y)²-4(x-2y)-13

Here is your answer :

Let (x - 2y) = a

then,

9(x-2y)²-4(x-2y)-13

= 9a² - 4a - 13

by using middle term splitting method

we can split 4a to 13a - 9a

So 9a² - 4a - 13

= 9a² - ( -9a +13a ) - 13

= 9a² + 9a - 13a - 13

= 9a ( a + 1 ) - 13 ( a + 1 )

= ( 9a - 13 ) ( a + 1 )

by putting the value of "a" in it we will get

[9(x-2y)-13] [(x-2y)+1]

= (9x - 18y - 13) (x - 2y +1)

Hope this help

i had tried my best to give the answer in an easiest way. if u have any doubt u can ask me anytime.

Thank you

Similar questions